How to Defend Yourself against the War? The Nobility Efforts to Protect Seigniorial Towns during the Thirty Years‘ War (Wilhelm Slavata and Jindřichův Hradec 1631–1633) (Theatrum historiae, 2015)
Using the particular example, the contribution analyzes the defence strategies by means of which, in the early 1630s – in connection with the Saxon invasion of the Czech lands - Bohemian Obristkanzler Wilhelm Slavata attempted to protect his estates on the border of southern Bohemia and southern Moravia both from attacks of enemy troops and the soldiers passing through and staying in seigniorial services.
Keywords: the Czech lands; Early Modern Times; the Thirty Years‘ War; seigniorial towns; Wilhelm Slavata; defence strategies